2008
DOI: 10.1093/jac/dkn504
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the TREAT decision support system in an environment with a low prevalence of resistant pathogens

Abstract: The results of the study suggest that TREAT can improve the appropriateness of antimicrobial therapy and reduce the cost of side effects in regions with a low prevalence of resistant pathogens, however, at the expense of increased use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…[18,20,24,27,29,31,33,34,36,44,50,52,55,59,62] Values for cost of antibiotic use are summarised in Table 4. The unit of cost report varied making it difficult to measure the overall impact of CDS.…”
Section: Resultsmentioning
confidence: 99%
“…[18,20,24,27,29,31,33,34,36,44,50,52,55,59,62] Values for cost of antibiotic use are summarised in Table 4. The unit of cost report varied making it difficult to measure the overall impact of CDS.…”
Section: Resultsmentioning
confidence: 99%
“…We found that most work has been conducted in relation to CPOE and CDS systems, focusing on interventions that targeted individual prescribers through prompts and reminders …”
Section: Resultsmentioning
confidence: 99%
“…Features of such systems deemed critical for improving clinical practice included decision support provided automatically within the clinical workflow, given at the time and location of decision-making, and that is computer-generated [11]. Antibiotic computerised decision support systems (CDSSs) incorporating these critical features have been developed to facilitate optimal antibiotic prescribing [12][13][14][15][16]. Antibiotic CDSSs are particularly useful for antibiotic selection for empirical therapy, as optimal selection is complex when the causative pathogen is as yet unknown and it is when the greatest discordance with recommended antibiotic guidelines occurs [17,18].…”
Section: Introductionmentioning
confidence: 99%